A case study of the sound environment in the one-to-one instructional spaces of a literacy center in relation to children with autism spectrum disorder - De Guzman, Abigail Z.
The case study aimed to assess the sound environment of the one-on-one instructional spaces of a literacy center in relation to children with ASD by describing the current conditions of a literacy center for children with ASD, comparing it to evidence-based auditory design guidelines, and analyzing the relationship of the sound environment to the students with ASD's behavior. Through a deductive case study research design with both qualitative and quantitative methods, a site observation, two interviews, a non-participant observation, and a survey were conducted. Purposive sampling was used for selection of the literacy center and the key informants while total population purposive sampling method was used to determine the survey respondents. The participants included one (2) key informants, which were the head and a student of the institution, respectively, and four (4) teachers as survey respondents. The sound in the instructional areas were studied in terms of background noise, echo, and reverberation while acoustical strategies were studied in terms of absorbers, blockers, and cover-ups. Results of the study show that the sound environment attributes of the one-on-one instructional spaces of the chosen literacy center of ASD are composed of exterior background noise from vehicles from the adjacent road, interior background noise from the air conditioner, reverberation through the wooden furniture, and echo from within the instructional, when occupied. Additionally, the acoustic strategies applied were incidental, for they were only results of basic construction and teaching materials, and not due to any guidelines followed. Findings show that the literacy center should alter each of their instruction rooms to cater to hyper-auditory sensitive students and hypo-auditory students, respectively.